The LILI Motif of M3-S2 Linkers Is a Component of the NMDA Receptor Channel Gate - Ladislav, Marek; Cerny, Jiri; Krusek, Jan; Horak, Martin; Balik, Ales; Vyklicky, Ladislav (Frontiers in Molecular Neuroscience, 2018)
N-methyl-D-aspartate receptors (NMDARs) mediate excitatory synaptic transmission in the central nervous system, underlie the induction of synaptic plasticity, and their malfunction is associated with human diseases. Native NMDARs are tetramers composed of two obligatory GluN1 subunits and various combinations of GluN2A-D or, more rarely, GluN3A-B subunits. Each subunit consists of an amino-terminal, ligand-binding, transmembrane, and carboxyl-terminal domain. The ligand-binding and transmembrane domains are interconnected via polypeptide chains (linkers). Upon glutamate and glycine binding, these receptors undergo a series of conformational changes leading to the opening of the Ca2+-permeable ion channel. Here we report that different deletions and mutations of amino acids in the M3-S2 linkers of the GluN1 and GluN2B subunits lead to constitutively open channels. Irrespective of whether alterations were introduced in the GluN1 or the GluN2B subunit, application of glutamate or glycine promoted receptor channel activity; however, responses induced by the GluN1 agonist glycine were larger, on average, than those induced by glutamate. We observed the most prominent effect when residues GluN1(L657) and GluN2B(I655) were deleted or altered to glycine. In parallel, molecular modeling revealed that two interacting pairs of residues, the LILI motif (GluN1(L657) and GluN2B(I655)), form a functional unit with the TTTT motif (GluN1(T648) and GluN2B(T647)), described earlier to control NMDAR channel gating. These results provide new insight into the structural organization and functional interplay of the LILI and the TTTT motif during the course of NMDAR channel opening and closing.